KEANEKARAGAMAN SPESIES KUPU-KUPU DI BLOK PEMANFAATAN KAWASAN HUTAN LINDUNG PUNCAK CEMARA KECAMATAN SUELA - Ariyaningsih, Puspita; Hadi, Islamul; Sari, Diah Permata (Jurusan Kehutanan, 2022)
The purpose of this study was to determine the diversity of butterfly species in the Puncak Cemara Protected Forest Area. Butterfly diversity is the number of species present at any one time in a particular community. The butterfly (Rhopalocera) is a species of insect belonging to the order Lepidoptera which means it has scales. This research was conducted in the forest area of Puncak Cemara Block utilization of the East Rinjani KPH. This study uses the Time Search method which is used to determine the diversity of butterflies using a plot with a specified time unit. This method does not have a distance limit but uses a predetermined time limit consistently. In this study, the time limit used was 15 minutes for each plot. This study used four different habitat types to compare the value of butterfly diversity. The results obtained in the Block Utilization of the Puncak Cemara Protected Forest Area found 37 butterfly species consisting of five families with a total of 361 individuals. Based on the calculation results, the path with the highest level of diversity is in the Secondary Forest path (H'=2,636). The path with the highest level of wealth is in the Secondary Forest path (Dmg=3,860). The path with the highest evenness was in the Primary Forest (E=0.897), while the path with the highest level of species similarity was in the Secondary and Riparian Forest (Q=0.33). Based on the results of the dominance analysis, the butterfly categorized as the dominant species is the Cepora judith butterfly.